Truth struggles? Capitalist State and Pandemic (Part 2) (PROKLA. Journal of Critical Social Science, 2022)
The second part of the article (the first was published in PROKLA 206) deals with the organization of knowledge by the bourgeois state in the corona pandemic. The thesis is that the state needs knowledge in order to manage social processes and must also limit the dynamics of this knowledge, because otherwise aspects that threaten to endanger capital utilization and order themselves could enter into political decisions. The assertion that democracy and science are in conflict with one another and that the latter endangers democracy is denied.
Keywords: Experts; Intellectuals; Power; Democracy; Reason; Relativism; Covid-19